Society 5.0 A People-centric Super-smart Society (Springer Nature, 2020)
This open access book introduces readers to the vision on future cities and urban lives in connection with "Society 5.0", which was proposed in the 5th Basic Science and Technology Plan by Japan's national government for a technology-based, human-centered society, emerging from the fourth industrial revolution. The respective chapters summarize the findings and suggestions of joint research projects conducted by H-UTokyo Lab. Through the research collaboration and discussion, this book explores the future urban lives under the concept of "Society 5.0", characterized by the key phrases of data-driven society, knowledge-intensive society, and non-monetary society, and suggests the directionality to which the concept should aim as Japan's technology-led national vision. Written by Hitachi's researchers as well as academics from a wide range of fields, including engineering, economics, psychology and philosophy at The University of Tokyo, the book is a must read for members of the general public interested in urban planning, students, professionals and researchers in engineering and economics.